2021
DOI: 10.3389/fmicb.2021.634539
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Significance of the Neuroendocrine Stress Axis on Vertebrate Immunity and the Influence of the Microbiome on Early-Life Stress Regulation and Health Outcomes

Abstract: Stress is broadly defined as the non-specific biological response to changes in homeostatic demands and is mediated by the evolutionarily conserved neuroendocrine networks of the hypothalamus-pituitary-adrenal (HPA) axis and the sympathetic nervous system. Activation of these networks results in transient release of glucocorticoids (cortisol) and catecholamines (epinephrine) into circulation, as well as activation of sympathetic fibers innervating end organs. These interventions thus regulate numerous physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 348 publications
(296 reference statements)
0
10
0
Order By: Relevance
“…This may lack face and construct validity, and it is not designed to model a specific disease mechanism. Nonetheless, it does measure HPI axis stress responses and the neuroendocrine and monoamine control systems underlying the stress axis is conserved from chordates to mammals 82 , moreover locomotor activity in zebrafish larvae is inherently cortisol dependent 12 . A similar approach has been used to identify novel anti-psychotic compounds in zebrafish larvae 15 , and to investigate the paradoxical excitatory effects of GABA and serotonin 16 , for example.…”
Section: Discussionmentioning
confidence: 99%
“…This may lack face and construct validity, and it is not designed to model a specific disease mechanism. Nonetheless, it does measure HPI axis stress responses and the neuroendocrine and monoamine control systems underlying the stress axis is conserved from chordates to mammals 82 , moreover locomotor activity in zebrafish larvae is inherently cortisol dependent 12 . A similar approach has been used to identify novel anti-psychotic compounds in zebrafish larvae 15 , and to investigate the paradoxical excitatory effects of GABA and serotonin 16 , for example.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in brain stress responses, sports, anxiety, and social behavior are thought to be linked to the gut microbiota ( 41 44 ). The vulnerability of the stress response network to maladaptive development was demonstrated by modeling animal models to explore the interaction between the activation of intestinal flora in the HPA axis of stress response and brain response ( 45 ). The HPA axis has long been thought to play a key role in regulating the balance of hormone secretion ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most vertebrates, cortisol is the main circulating glucocorticoid released during a primary stress response. This hormone is critical for mediating the stress response and can induce both behavioral and metabolic pleiotropic effects ( Ortega et al, 2021 ), and it is a classic marker for its evaluation. In Atlantic salmon, the previous studies have shown a typical pattern for this molecule.…”
Section: Discussionmentioning
confidence: 99%